(untitled) - Bannister, Karyl (Boston, MA., 2001)
After sharing amateur family-style recipes for 20 years in a newsletter of the same title, Bannister compiles her favorites in book form, garnishing them with homey anecdotes, tips from the newsletter's subscribers and her own appealing miniature illustrations. Many of the recipes are named for the subscribers who submitted them Betty's Quick Coffee Cake, Angie's Cold Broccoli giving the book a disarming sewing-circle feel. Bannister's recipes are unremarkable, but quick and undemanding; they typically exhort the reader to not worry too much about technique. Some combine wholesome, fresh ingredients, but most make use of commercially prepared foods such as the canned vegetables or sauces easily found in mainstream grocery stores. Many of the recipes are classics, such as the Simple Shepherd's Pie, Spareribs and Sauerkraut and Cranberry-Glazed Pork Roast. Desserts and baked goods are the strongest offerings, with some truly outstanding, like the Linzertorte, Trifle and Irish Oat Scones. Bannister's paramount assumption is that quickly executing a hot meal for the family is the overriding demand on the average home cook; the success of many of these recipes thus relies on somewhat diminished expectations. The planned six-city author tour may help her overcome slumming cosmopolitans' fear of canned goods. Agent, Doe Coover. B&w illus.
Keywords: Quick and easy cookery